Application of innovative teaching methods in teaching of entrepreneurship in the Nigerian polytechnichs - Dahiru, Abbas Sani; Lope Pihie, Zaidatol Akmaliah (Marsland Press, 2016)
Entrepreneurship education is intended to communicate and instil skills, abilities, understanding, and values required to identify business opportunity, establish and start new business project. It involves translating an idea into reality. However, selecting the appropriate teaching methods required meeting up with the course objectives and the needs of the students had become a challenge to lecturers in the Nigerian Polytechnics. Thus, this paper discussed the concept of entrepreneurship education, entrepreneurship education in Nigeria, pedagogical approaches in teaching entrepreneurship education, and finally the implications of the paper on both the practitioners and policy makers were discussed.